The drunk diet : how I lost 40 pounds . . . wasted : a memoir - Carl, Lüc (St. Martin's Press, 2012)
"Full of charismatic wit and raucous stories about his life, The Drunk Diet will inspire and challenge you to become fitter, healthier, and happier. Lüc's fitness philosophy isn't about following a list of rigid rules or traditional 'do this, not that' charts, but gaining a better understanding of how the body works and discovering what you're personally willing to change about your lifestyle in order to reach your goals. For him, that meant trading in the crap he was eating for unprocessed, natural foods and embracing a newfound love for exercise, but never sacrificing his social life (or his love for cold beer)."--dust jacket.